2021
DOI: 10.1002/asi.24534
|View full text |Cite
|
Sign up to set email alerts
|

Digital humanities as a cross‐disciplinary battleground: An examination of inscriptions in journal publications

Abstract: Inscriptions are defined as traces of scientific research production that are embodied in material artifacts and media, which encompass a wide variety of nonverbal forms such as graphs, diagrams, and tables. Inscription serves as a fundamental rhetorical device in research outputs and practices. As many inscriptions are deeply rooted in a scientific research paradigm, they can be used to evaluate the level of scientificity of a scientific field. This is specifically helpful to understand the relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Benito-Santos and Therón Sánchez [9] deployed a data-driven approach and focused on a bibliographic analysis of the research community focusing on the collaboration networks among authors and the publication topics. Also focusing on collaborations, Ma and Li [84] reviewed the various inscriptions that digital humanities use, including data visualizations. They found that inscription-use seems to be driven by the increase of interdisciplinary collaborations among humanists and STEM researchers.…”
Section: Surveying Visualization In the Humanitiesmentioning
confidence: 99%
“…Benito-Santos and Therón Sánchez [9] deployed a data-driven approach and focused on a bibliographic analysis of the research community focusing on the collaboration networks among authors and the publication topics. Also focusing on collaborations, Ma and Li [84] reviewed the various inscriptions that digital humanities use, including data visualizations. They found that inscription-use seems to be driven by the increase of interdisciplinary collaborations among humanists and STEM researchers.…”
Section: Surveying Visualization In the Humanitiesmentioning
confidence: 99%
“…More specifically, exploratory tools that facilitate interactive discovery, analysis, or visualization, have been widely deployed in digital collections and projects as an essential feature to support indepth, creative interaction with the digital materials. Such exploratory tools in the context of digital humanities collections and projects can include, for example, visual analytic applications that allow users to explore the collection data broadly in the interface by means of visualization, or analytic applications embedded in interfaces that empower users to critically engage with the resources, performing interpretative activities of data, and sharing analysis and results via different scholarly communication channels (Gibbs and Owens, 2012;McCurdy et al, 2016;Jänicke et al, 2017;Chen et al, 2019;Chen & Cole, 2021;Ma, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in the landscape of DH illustrated that "DH is simultaneously a discipline in its own right and a highly interdisciplinary field, with many connecting factors to neighboring disciplines-first and foremost, computational linguistics, and information science" (Luhmann & Burghardt, 2022). In addition to the roles of DH among academic fields, Ma and Li (2022) also demonstrated that humanities and STEM researchers, among others, further shape the DH community with their respective, sometimes competing, research conventions as well as cross-field research collaborations. Empirical works focusing on DH intellectual structures, disciplinary compositions, and collaboration also suggest an increasingly complex picture of DH workforce (Antonijević, 2015;Fiormonte et al, 2015;Griffin & Hayler, 2018;Papadopoulos & Reilly, 2020).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%